Detecting subsidence spatial risk distribution of ground deformation induced by urban hidden streams. Issue 6 (8th March 2021) - Krassakis, Pavlos; Kazana, Stavroula; Chen, Fulong; Koukouzas, Nikolaos; Parcharidis, Issaak; Lekkas, Efthymios
Abstract: A plethora of subsidence events has been repeatedly reported in high density urban environments. The purpose of this study is to introduce specific areas around the riverbeds of the urban hidden streams in the city of Athens presenting high risk in terms of ground subsidence. The study area comprises the centre of Athens and more specifically the Municipalities of Athens, Tavros, Kallithea, Daphne, Hymettus and Ilisia where the ancient rivers of Ilissos and Eridanus naturally flow through a heavily populated city. It wasn't until the early 1960s that the two rivers were completely channelled and partly covered along their course during the urbanization process which allowed the construction of the modern boulevards, roads, recreation and open space areas as long as parking areas. The route of today's concealed rivers and streams poses a serious risk of potential ground subsidence concerning the erosion of streams' bank permeable soil formations. Following this approach, areas of influence (buffer zones) were determined on each side of the subterranean urban rivers Ilissos and Eridanus. In particular, an inventory of literature and references such as, historical maps and drawings, technical studies as well as modern topographic and geological maps, land use/land cover maps were created and collected in a geospatial database. It is worth mentioning that a main part of this study was the utilization and analysis of satellite radar data of the time period 2012–2016, in order to detect vertical displacements (mm/year) and correlate these with the above-mentioned spatial data of Athens city.